The Association of Non-obscene Socially Inappropriate Behavior With Attention-Deficit/Hyperactivity Disorder Symptoms, Conduct Problems, and Risky Decision Making in a Large Sample of Adolescents - Brandt, Valerie; Kerner auch Koerner, Julia; Palmer-Cooper, Emma (Frontiers in Psychiatry, 2019)
Non-obscene, socially inappropriate behavior (NOSI) is recognized as part of the tic disorder spectrum but has received little attention from researchers to date. A study in 87 patients with Tourette Syndrome showed that comorbid ADHD and conduct disorder were also associated with an increase in socially inappropriate behavior. This study used data from the Millennium Cohort Study to investigate the relationship between NOSI and emotional symptoms, conduct problems and hyperactivity /inattention as assessed by the Strengths and Difficulties Questionnaire (SDQ) in 1280 youths, aged 14 years. Furthermore, the relationship between NOSI and decision making processes as assessed by the Cambridge Gambling Task (CGT) was investigated. Hyperactivity /inattention and conduct problems were significantly associated with NOSI, emotional problems were not. Risk taking was significantly associated with misbehaving in lessons but not with being rude or noisy in public. The results replicate and confirm the association of NOSI with ADHD and conduct problems in a large sample, although it should be stressed that the size of the association was small. The results also suggest that some inappropriate behaviors are related to risk taking behavior, while others are not.